Immunoglobulin J chain as a non-invasive indicator of pregnancy in the cheetah (Acinonyx jubatus). - Michael J Byron; Diana C Koester; Katie L Edwards; Paul E Mozdziak; Charlotte E Farin; Adrienne E Crosier (PLoS ONE, 2020)
The North American cheetah population serves as a reservoir for the species, and acts as a research population to help understand the unique biology of the species. Little is known about the intrauterine physiology of the cheetah, including embryo differentiation, implantation, and the development of the placenta. After mating, cheetah females frequently experience (30-65% of matings) a non-pregnant luteal phase where progestogen metabolite levels match those found in pregnant females for the first ~55 days of gestation, but parturition does not occur. Immunoglobulin J chain (IgJ) is a molecule that is involved in the activation of the secretory immune response and has been found to be indicative of pregnancy in the cheetah using fecal monitoring. In this study, western blotting was employed to track IgJ abundance in pooled weekly fecal samples following natural breeding or exogenous stimulation to ovulate, and IgJ levels were compared between individuals undergoing a pregnant (n = 12) and non-pregnant (n = 19) luteal phase. It was revealed that IgJ abundance was increased in pregnant females compared to non-pregnant females at week 4 and week 8 post-breeding, indicating the potential modulation of maternal immunity in response to sensitive events such as implantation and the increased secretory activity of the placenta. IgJ levels also tended to be higher early after breeding in females that were bred naturally with intact males compared to exogenously stimulated females with no exposure to seminal plasma, potentially indicating a response to the act of intromission or the stress of breeding, or possibly demonstrating an immune response resulting in the promotion of maternal tolerance to seminal antigens present upon embryonic implantation. Monitoring fecal IgJ may be a potential method to determine gestational status in the cheetah and will aid future conservation efforts of the species.